DYEING OF COTTON FABRIC WITH NATURAL DYE FROM CUDRANIA JAVANENSIS USING SOKA LEAVES EXTRACT AS BIOMORDANT - Darsih, Cici; Lestari, Dwi Wiji; Pratiwi, Diah; Indrianingsih, A Wheni; Rosyida, Vita Taufika; Apriana, Wuri; Nisa, Khoirun; Hayati, Septi Nur; Handayani, Sri; Wulanjati, Martha Purnami (Balai Besar Standardisasi dan Pelayanan Jasa Industri Kerajinan dan Batik, 2019)
Tegeran wood (Cudrania javanensis) has been used for dyeing process of batik in Indonesian textile small medium scale enterprise. This wood gave soga color when it was mixed with others natural dye. This study was aim to evaluate the caharacteristic, fastness properties, and strength color of dyed cotton fabrics using C. javanensis with bio-mordant soka leaves extract. Extraction of C. javanensis was carried out using water. The post mordant process was carried out by applying alum (KAl(SO4)2•12H2O) solution and soka leaves extract on cotton fabrics with the concentration of 0.5 and 1% b/v. Characteristic of dyed cotton fabrics then was evaluated using Fourier-Transform Infrared (F-TIR) Spectroscopy. The results exhibited that, binding between tegeran wood on cotton using mordant alum and soka leaves extract was similar.The fastness properties both dyed cottons toward light and washing at 40ºC exhibited poor and very poor values with values of 1-2 and 1. The dry and wet rubbing of dyed cotton using soka leaves extract mordant better than using alum. The soka leaves extract gave yellow and brightness color on cotton.The results suggested that soka leaves extract can be used as mordant substitute the alum mordant and apllied with others natural dyes.